Implementasi Program Adiwiyata terhadap Sikap Peduli Lingkungan pada Siswa SMAN 4 Bogor - Novrizal, Alfian (Sosio-Didaktika: Social Science Education Journal, 2023)
The Adiwiyata program implemented in schools can help create conditions for schools to become comfortable, good and culturally environmentally friendly places to study. The Adiwiyata program implemented at SMAN 4 Bogor is supported by activities that support the school to help and foster an attitude and sense of caring for the environment. Activities carried out in collaboration with all school members in order to increase awareness of the cleanliness and comfort of the school environment. The research carried out aims to find out and obtain information about how the Adiwiyata Program is implemented at SMAN 4 Bogor. This research uses a qualitative descriptive research method as well as data collection techniques using several instruments consisting of interview activity data, documentation and observation. The results of this research show that SMAN 4 Bogor in implementing the Adiwiyata Program towards environmental caring attitudes in students can be said to be categorized as good and achieved, this is based on learning activities to the formation of Adiwiyata ambassadors and Adiwiyata cadres to help students in efforts to increase environmental caring attitudes.Keywords: Adiwiyata Program, Environmental Care Attitude, Students